2012
DOI: 10.1136/vr.100113
|View full text |Cite
|
Sign up to set email alerts
|

Activation procedures in the electroencephalograms of healthy and epileptic cats under propofol anaesthesia

Abstract: The current study evaluated the diagnostic value of electroencephalographic recordings (EEG) in cats with epilepsy under special consideration of photic stimulation and hyperventilation. EEGs in six healthy cats were recorded under light (mean dose of 0.23 mg/kg/min) and deep (mean dose of 0.7 mg/kg/min) propofol anaesthesia, whereas EEGs in 13 diseased cats were recorded under a propofol anaesthesia which was kept as light as possible (mean dose of 0.39 mg/kg/min). Paroxysmal discharges were detected in six o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 37 publications
1
6
1
Order By: Relevance
“…A high proportion of the cats with EUC in this study showed CPS with orofacial involvement and a good outcome, similar to what has been described recently in correlation with FHN . FHN previously has been described as a frequent etiology for seizures in cats whereas others only observed it infrequently . When reviewing and comparing the MRI scans from cats with EUC and cats without seizures, we were unable to confirm hippocampal signal alterations in any of the cats in the study.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…A high proportion of the cats with EUC in this study showed CPS with orofacial involvement and a good outcome, similar to what has been described recently in correlation with FHN . FHN previously has been described as a frequent etiology for seizures in cats whereas others only observed it infrequently . When reviewing and comparing the MRI scans from cats with EUC and cats without seizures, we were unable to confirm hippocampal signal alterations in any of the cats in the study.…”
Section: Discussionsupporting
confidence: 62%
“…Epilepsy of unknown cause was diagnosed in 22% of cats with recurrent seizures. This frequency is less than previously reported (25, 38, 41, and 54, 66%) by other authors, who had called this entity idiopathic or presumed idiopathic seizures, suspected idiopathic epilepsy, probable symptomatic epilepsy, or primary epilepsy . However, in this study, all cats with epilepsy of unknown cause and structural epilepsy were examined by 1.5 T MRI or underwent PME.…”
Section: Discussioncontrasting
confidence: 54%
“…Brainstem auditory evoked response [modified according to Plonek et al ( 12 )] showed normal wave I, III and V latencies on both sides. Electroencephalography [modified according to Brauer et al ( 13 )] displayed sporadic spikes, a constant underlying beta rhythm and occasionally muscle artifacts caused by swallowing. The cat did not regain consciousness or spontaneous breathing within 12 h of mechanical hypocapnic ventilation and after mannitol bolus infusion (1 g/kg i. v.).…”
Section: Casesmentioning
confidence: 99%
“…There are only limited data relating to clinical EEG in healthy cats and cats with recurrent seizures . Recently encouraging EEG results were reported in cats . Under propofol restrain, 6 of 13 epileptic cats showed paroxysmal discharges (focal or generalized spikes), while such activity was not detected in any of 6 healthy control cats.…”
Section: Diagnostic Evaluation Of a Cat With Suspected Epileptic Seizurementioning
confidence: 99%